Business organization and management - Medina, Roberto G. (Manila, Philippines : Rex Book Store, 2006)
Writing a book is like manufacturing a product. Both the author and the manufacturer hope that majority, if not all, of the target customers will like what they get. Although good intentions do not always satisfy everybody, it must not deter the author or the manufacturer from doing what he thinks is necessary. This book i designed as a beginner's course in business management. Even if the course description of the subject "Business Organization and Management" varies from school to school, it is hoped that at least the minimum requirements of each description will be met. The first chapter of the book deals with the basic foundations of business. The second chapter presents "Ethics and Social Responsibility", a very relevant topic. The succeeding chapters deal with the management functions of decision-making, planning, organizing, staffing, communicating, motivating, leading, and controlling. The final chapters cover areas of management, such as production and service operations, marketing and finance. The book contains presentations of theories and principles in relating to organization and management."
CHAPTER 1. The foundations of business -- 2. Ethics and social responsibility 16 -- 3. Forms of business ownership -- 4. Decision-making -- 5. Planning -- 6. Organizing business activities -- 7. Staffing the organization -- 8. Communicating -- 9. Motivating -- 10. Leading -- 11. Controlling -- 12. Managing production and service operations -- 13. Managing the marketing function -- 14. Managing the finance function.
Includes bibliographical references and index.
Keywords: BUSINESS